Nickel-based alloy material surface modification method based on pulse laser
Through the surface modification method of nickel-based alloy material based on pulsed laser, the surface morphology and wettability of nickel-based alloy mesh materials are optimized, and the problem of low filtration efficiency of existing nickel-based alloy mesh materials is solved, achieving more efficient filtration effect and production efficiency.
Patent Information
- Application Number
- CN202411662247.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The filtration efficiency of existing nickel-based alloy mesh materials is low and the filtration effect is poor. It is necessary to adjust the nanosecond pulse laser processing parameters to improve production efficiency and reduce costs.
Using the surface modification method of nickel-based alloy material based on pulsed laser, the optimal laser processing process parameters are sought through ultrasonic cleaning and drying, designing processing sizes and parameters, conducting preliminary processing and measurement, wetting experiments and process parameter optimization. Group.
Through the modification treatment, the surface morphology, pore area size, element content and wettability of the nickel-based alloy mesh material are optimized, which significantly improves the filtration efficiency and effect, and provides a basis for efficiency improvement and cost reduction for industrial production.
Smart Images

Figure CN119426804A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanosecond pulse laser modification and relates to a surface modification method of a nickel-based alloy material based on pulse laser. Background Art
[0002] Nickel-based alloy mesh materials mainly play the role of filtering chloride ions in industrial production, and the excellent filtering effect determines the efficiency and cost of industrial production. Compared with nickel-based alloy mesh materials that have not been modified by nanosecond pulse laser, the modified nickel-based alloy mesh materials have obtained an ideal micro-texture morphology, smaller pore area, higher oxygen content, and good hydrophilicity on the surface of the material. These changes will make the nickel-based alloy mesh materials achieve better results in the filtering process. Laser surface modification technology is a unique and effective surface treatment technology with the advantages of high control accuracy, fast processing speed, and low pollution.
[0003] The existing nickel-based alloy mesh materials have low filtration efficiency and poor filtration effect in industrial production. It is particularly important to obtain the optimal laser processing parameter group by continuously adjusting the nanosecond pulse laser processing parameters to process the nickel-based alloy mesh materials in order to improve production efficiency and reduce production costs. Summary of the invention
[0004] The purpose of the present invention is to provide a method for surface modification of nickel-based alloy materials based on pulsed laser, which solves the problem that the nickel-based alloy mesh materials prepared by the prior art have low filtration efficiency and poor filtration effect.
[0005] The technical solution adopted by the present invention is a method for surface modification of nickel-based alloy materials based on pulsed laser, which is implemented according to the following steps: Step 1, ultrasonically cleaning and drying the nickel-based alloy mesh material to be processed; Step 2, installing the nickel-based alloy mesh material into the laser processing system to complete the pre-processing preparation work; Step 3, importing the designed processing dimensions into the laser processing system, setting preliminary processing parameters, performing preliminary processing, and measuring and comparing the nickel-based alloy mesh material after preliminary processing; Step 4, performing a wettability test on the preliminarily processed nickel-based alloy mesh material to analyze the effects of different processing parameters on the wettability of the material; Step 5, according to the filtering requirements of the nickel-based alloy mesh material and the influence of the content of each element in the material on the service life, continue to optimize and adjust the process parameters during the nanosecond pulse laser processing to find the optimal laser processing process parameter group.
[0006] The beneficial effect of the present invention is that the surface of the nickel-based alloy mesh material is modified by a nanosecond pulse laser, and various detection, analysis and comparison are performed on the material after the experiment, so as to obtain the optimal nanosecond pulse laser processing process parameter group, providing a basis for improving efficiency and reducing production costs in industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 Original micrograph of the nickel-based alloy mesh material used in the method of the present invention; Figure 2a It is the surface morphology of the material when the processing power is 35W in Example 1 of the method of the present invention; Figure 2b It is the surface morphology of the material when the processing power is 38W in Example 1 of the method of the present invention; Figure 2c It is the surface morphology of the material when the processing power is 41W in Example 1 of the method of the present invention; Figure 2d It is the surface morphology of the material when the processing power is 44W in Example 1 of the method of the present invention; Figure 2e It is the surface morphology of the material when the processing power is 47W in Example 1 of the method of the present invention; Figure 2f is the surface morphology of the material when the processing power is 50 W in Example 1 of the method of the present invention; Figure 3a This is the micro-texture morphology of the material when the processing speed is 25 mm / s in Example 2 of the present invention; Figure 3b This is the micro-texture morphology of the material when the processing speed is 30 mm / s in Example 2 of the present invention; Figure 3c This is the micro-texture morphology of the material when the processing speed is 35 mm / s in Example 2 of the present invention; Figure 3d This is the micro-texture morphology of the material when the processing speed is 40 mm / s in Example 2 of the present invention; Figure 3e This is the micro-texture morphology of the material when the processing speed is 45 mm / s in Example 2 of the present invention; Figure 3f This is the micro-texture morphology of the material when the processing speed is 50 mm / s in Example 2 of the present invention; Figure 4a is the surface wettability of the material when the pulse width is 250ns in Example 3 of the present invention; Figure 4b is the surface wettability of the material when the pulse width is 300 ns in Example 3 of the present invention; Figure 4c is the surface wettability of the material when the pulse width is 350ns in Example 3 of the present invention; Figure 4dis the surface wettability of the material when the pulse width is 400 ns in Example 3 of the present invention; Figure 4e is the surface wettability of the material when the pulse width is 450ns in Example 3 of the present invention; Figure 4f It is the surface wettability of the material when the pulse width is 500ns in Example 3 of the present invention.
[0008] Figure 5 is a curve showing the change of the pore area size of the material with the repetition frequency in Example 4 of the present invention; Figure 6 This is a curve showing the change in the material element content with the number of laser processing times in Example 5 of the present invention. DETAILED DESCRIPTION
[0009] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0010] The method of the present invention relies on a laser processing system, the main structure of which is that a stage and a high-precision rotating ruler are arranged on the upper surface of the workbench, the upper surface of the stage is used to place the nickel-based alloy mesh material to be processed, a nanosecond pulse laser is arranged on the column of the rotating ruler, the laser beam emitted by the nanosecond pulse laser is directly irradiated downward on the upper surface of the nickel-based alloy mesh material, and the rotating ruler is equipped with a control mechanism, which includes a computer, a display, and a control panel.
[0011] The surface modification method of nickel-based alloy material based on pulsed laser of the present invention is implemented by using the above-mentioned laser processing system according to the following steps: Step 1, ultrasonically cleaning and drying the nickel-based alloy mesh material to be processed; The ultrasonic cleaning machine model is JP-020S, which is a mechanical device that uses high-frequency sound waves to produce cavitation in liquids to achieve the purpose of cleaning. The bubbles in the ultrasonic cleaning machine grow rapidly and burst suddenly under the action of ultrasonic waves, generating extremely strong impact force, which completely removes stains, oil stains, dirt and other impurities on the surface of the nickel-based alloy mesh material and in the tiny gaps.
[0012] Step 2, installing the nickel-based alloy mesh material into the laser processing system to complete the pre-processing preparation work; The nickel-based alloy mesh material after ultrasonic cleaning is placed flat on the stage, and the nickel-based alloy mesh material is pressed and fixed by two pressure plates on the stage to prevent displacement during nanosecond pulse processing and affect the experimental results; then turn on the main switch of the nanosecond pulse laser, turn on the key switch on the control panel, and after the value displayed on the DC voltage stabilizes, start the computer and turn on the laser processing system on the monitor; then, focus by continuously adjusting the rotating ruler. When the focal length of the laser beam is adjusted, lock the rotating ruler by rotating the wrench to complete the processing preparation work for the nickel-based alloy mesh material.
[0013] Step 3, importing the designed processing dimensions into the laser processing system, setting preliminary processing parameters, scanning the surface of the nickel-based alloy mesh material with a nanosecond pulse laser beam, performing preliminary processing, and measuring and comparing the nickel-based alloy mesh material after preliminary processing; The specific process is: First, open the control software of the nanosecond pulse laser and input the pattern information to be processed (for example, a 10mm×10mm square pattern); Then, the preliminary processing parameters of the nanosecond pulse laser are set: the filling mode is unidirectional filling, the filling spacing is 10 μm, the processing power is 10-60 W, the processing speed is 10-50 mm / s, the repetition frequency is 20-30 kHz, the pulse width is 100-500 ns, and the number of processing is 1-10 times; after setting the parameters, the preliminary processing is carried out; After that, the nickel-based alloy mesh material that has completed the preliminary processing is measured and analyzed, including the following three aspects: First, a laser confocal microscope (model LEXT OLS4000) was used to observe and analyze the surface morphology; second, a high-precision imager (model Tianzhun VMZ) was used to measure the pore area size; third, an electron microscope (model VEGA II XMU scanning electron microscope produced by Czech TESCAN) was used to observe and analyze the element content and the morphology of the surface microtexture.
[0014] Step 4, performing a wettability test on the preliminarily processed nickel-based alloy mesh material to analyze the effects of different processing parameters on the wettability of the material; The wettability test experiment uses a contact angle tester. The experimental process is: the nickel-based alloy mesh materials under different laser processing parameters after preliminary processing are placed on the detection platform respectively, and after adjusting the position and camera focus, 5μL of pure water droplets are taken through a microsampler on the surface of the nickel-based alloy mesh material after preliminary processing. When the droplets spread on the micro-texture surface of the nickel-based alloy mesh material and tend to a stable state, the contact angle tester is used to measure the solid-liquid contact angle on the surface of the nickel-based alloy mesh material.
[0015] By conducting wettability experiments on nickel-based alloy mesh materials after preliminary processing, the following conclusions were obtained: Under different laser processing parameters, the larger the spacing between the obtained micro-textures, the stronger the surface hydrophilicity of the material, the higher the filtration efficiency of the material, and the better it can achieve time saving in the industrial production process.
[0016] The preliminary processing and result detection analysis of nickel-based alloy mesh materials using nanosecond pulse lasers have been completed. Since some laser processing parameters have too much or no effect on the material, it is necessary to refine the reasonable laser processing parameters, repeat the experiment, and seek the optimal laser processing parameter group.
[0017] Step 5, according to the filtering requirements of the nickel-based alloy mesh material and the influence of the content of each element in the material on the service life, continue to optimize and adjust the process parameters in the nanosecond pulse laser processing process to find the optimal laser processing process parameter group; According to the changing rules of surface morphology, pore area size, element content, surface microtexture morphology and wettability of nickel-based alloy mesh materials, the single factor variable method was adopted, keeping all other variables unchanged, and the influence of each variable on the result was studied in turn. Through comparative analysis, the ideal combination of laser processing process parameters was finally obtained.
[0018] Example 1 This embodiment 1 is based on the above-mentioned method of the present invention and is implemented according to the following steps: Step 1: ultrasonically clean and dry the nickel-based alloy mesh material.
[0019] First, make sure the cleaning machine is placed in a clean and dry environment and avoid severe vibration. Next, check whether the power supply, switch, indicator light and indicator meter are working properly. Clean the cleaning tank and pour the cleaning liquid into the cleaning tank according to the liquid level in the instructions. Add water to the cleaning tank of the ultrasonic cleaning machine. The water level must not exceed the upper limit. Put the nickel-based alloy mesh material into the ultrasonic cleaning machine, turn on the power switch of the ultrasonic cleaning machine, and set the ultrasonic cleaning temperature, ultrasonic cleaning time, degassing time and other parameters. Rinse the cleaned nickel-based alloy mesh material with clean water and dry it to prevent the liquid remaining in the nickel-based alloy mesh material from oxidizing it. Blow away the residual liquid on the nickel-based alloy mesh material, and refer to Figure 1 .
[0020] Step 2: placing the nickel-based alloy mesh material in a laser processing system.
[0021] Place the nickel-based alloy mesh material after ultrasonic cleaning flat on the stage, and then press and fix the nickel-based alloy mesh material through the two pressure plates on the stage to prevent the nanosecond pulse laser from shifting during the processing process and affecting the experimental results. Next, turn on the main switch of the nanosecond pulse laser, turn on the key switch on the control panel, and after the value displayed on the DC voltage stabilizes, start the computer and turn on the laser processing system on the monitor. Next, focus by continuously adjusting the high-precision rotating ruler. When the focal length of the laser beam is adjusted, lock the rotating ruler by rotating the wrench.
[0022] Step 3, importing the designed processing dimensions into the laser processing system, setting preliminary processing parameters, scanning the surface of the nickel-based alloy mesh material by nanosecond pulse laser, performing preliminary processing, and measuring and comparing the materials after preliminary processing; In the laser processing system, draw a 10mm×10mm square pattern, add filling, set the filling mode to unidirectional filling, set the line spacing to 10μm, close the default parameters, set the number of processing to 1-10 times, set the speed to 10-50mm / s, set the power to 10-60W, set the frequency to 20-30kHz, and set the pulse width to 100-500ns. Turn on the laser button on the controller and click the red light on the current display. At this time, a red 10mm×10mm square pattern appears on the surface of the nickel-based alloy mesh material. The area covered by the red is the area to be processed by the nanosecond pulse laser beam. Use the stage to translate the nickel-based alloy mesh material and adjust the processing area. Next, turn off the red light and click Mark to start modifying the surface of the nickel-based alloy mesh material.
[0023] The regularity of the surface morphology change of the material after preliminary processing was studied and observed using a laser confocal microscope model LEXT OLS4000. The processed nickel-based alloy mesh material was placed on the test platform, and the processed part was translated to the bottom of the camera lens through the laser confocal microscope. Next, the coarse focusing screw was adjusted for rough focus, and then the fine focusing screw was adjusted for accurate focus. The surface morphology presented on the display was saved and compared, and the change of the surface morphology with the processing parameters of the nanosecond pulse laser was summarized.
[0024] The regularity of the change of the pore area size of the material after preliminary processing was studied, and the Tianjue VMZ high-precision imager was used for measurement. The processed nickel-based alloy mesh material was placed on the test platform, and the X-axis and Y-axis of the high-precision imager were clicked by the mouse, the camera was placed above the material, and the autofocus was clicked. The Z-axis moved automatically to focus. When the focusing work was completed, all the lights of the imager were turned off, and the lights under the workbench were turned on. At this time, the pore part of the nickel-based alloy mesh material appeared white, and the material itself appeared black. At this time, it can be picked up and measured. Click the automatic pick-up range on the operation interface, select the measurement area, and click the pore part. At this time, the pore area size is measured. In order to ensure the accuracy of the experiment, 10 different positions were selected for each 10mm×10mm square pattern for measurement. When processing the data, the data with too large errors were removed, and then the average value was calculated. Finally, the change law of the pore area size with nanosecond pulse laser processing parameters was obtained.
[0025] The regularity of the element content and surface microtexture changes of the material after preliminary processing was studied, and the VEGA II XMU scanning electron microscope produced by Czech TESCAN was used for observation and analysis. In order to facilitate detection, the nickel-based alloy mesh material was first cut into a 10mm×10mm square pattern, the initial state of the electron microscope was adjusted, the cabin door was opened, the card slot was aligned, the nickel-based alloy mesh material was fixed, and the cabin door was closed. Return to the electron microscope interface, click on vacuum, then set the test material height, select the sample stage, and then manually slowly raise the sample stage. After adjustment, turn on the voltage, adjust the focus, and take the electron microscope image of the surface microtexture morphology of the nickel-based alloy mesh material after processing. At the same time, the changes in the content of each element in the nickel-based alloy mesh material also obtained corresponding results, focusing on the changes in nickel and oxygen elements. Finally, the change rules of the element content and surface microtexture morphology of the nickel-based alloy mesh material with the nanosecond pulse laser processing parameters were obtained.
[0026] Step 4: Conduct a wettability test on the nickel-based alloy mesh material after preliminary processing to analyze the effects of different processing parameters on the wettability of the material.
[0027] First, the contact angle tester is white-balanced, and after adjusting the light brightness and camera focal length, the processed nickel-based alloy mesh material is placed on the test platform, and an appropriate amount of pure water is drawn in through a micro-sampler, and then 5 μL of pure water is dropped on the surface of the processed nickel-based alloy mesh material. When the droplet spreads on the texture surface and tends to a stable state, the solid-liquid contact angle of the sample surface is measured by the contact angle meter, and the change in the wettability of the micro-textured surface is characterized. Next, the storage path is entered, and the photo is clicked to save the wettability picture. Next, the contact roughness meter is used to fit the surface profile through the software, and the angle between the droplet and the plane of the nickel-based alloy mesh material is measured to study the change in wettability of the nickel-based alloy mesh material after processing. Finally, the change law of material wettability with each processing parameter of nanosecond pulse laser is obtained.
[0028] Step 5: According to the filtering requirements of the nickel-based alloy mesh material and the influence of the content of each element in the material on the service life, the nanosecond pulse laser processing parameters are further optimized and adjusted to find the optimal laser processing parameter group.
[0029] Firstly, the filling mode of nanosecond pulse laser was set to unidirectional filling, the number of processing times was 3, the processing speed was 35 mm / s, the repetition frequency was 25 kHz, and the pulse width was 400 ns. Experiments were carried out with the increase of the processing power of nanosecond pulse laser (35 W, 38 W, 41 W, 44 W, 47 W, 50 W), and the experimental results were tested and compared and analyzed. Finally, the surface morphology, pore area size, element content, micro-texture morphology state and wettability of nickel-based alloy mesh material with processing power were obtained, as shown in Fig. Figure 2a is the surface morphology of the material when the processing power is 35W in Example 1; Figure 2b is the surface morphology of the material when the processing power is 38W in Example 1; Figure 2c is the surface morphology of the material when the processing power is 41W in Example 1; Figure 2d is the surface morphology of the material when the processing power is 44W in Example 1; Figure 2e is the surface morphology of the material when the processing power is 47W in Example 1; Figure 2f This is the surface morphology of the material when the processing power is 50W in Example 1.
[0030] From the results of Example 1, it can be found that the surface morphology of the nickel-based alloy mesh material after the modification treatment, as the laser processing power increases, the surface temperature of the material gradually increases, and thermal expansion occurs at certain intervals in the lateral direction. Each expansion point is the focus of the laser, the laser energy is the most intensive, and the volume of thermal expansion continues to increase.
[0031] Example 2 Steps 1 to 4 of Example 2 are the same as those of Example 1, except that: Step 5: According to the filtering requirements of the nickel-based alloy mesh material and the influence of the content of each element in the material on the service life, the nanosecond pulse laser processing parameters are further optimized and adjusted to find the optimal laser processing parameter group.
[0032] The filling mode of nanosecond pulse laser was set to unidirectional filling, the number of processing times was 3, the processing power was 41W, the repetition frequency was 25kHz, and the pulse width was 400ns. Experiments were conducted with the increase of the processing speed of nanosecond pulse laser (25mm / s, 30mm / s, 35mm / s, 40mm / s, 45mm / s, 50mm / s). The experimental results were tested and compared, and finally the surface morphology, pore area size, element content, micro-texture morphology state and wettability of nickel-based alloy mesh materials with processing speed were obtained. Figure 3a It is the micro-texture morphology of the material when the processing speed is 25 mm / s in Example 2; Figure 3b It is the micro-texture morphology of the material when the processing speed is 30 mm / s in Example 2; Figure 3c It is the micro-texture morphology of the material when the processing speed is 35 mm / s in Example 2; Figure 3d It is the micro-texture morphology of the material when the processing speed is 40 mm / s in Example 2; Figure 3e It is the micro-texture morphology of the material when the processing speed is 45 mm / s in Example 2; Figure 3f This is the micro-texture morphology of the material when the processing speed is 50 mm / s in Example 2.
[0033] From the results of Example 2, it can be found that the surface morphology of the nickel-based alloy mesh material after the modification treatment, as the processing speed increases, the time that the laser acts on the nickel-based alloy mesh material becomes shorter, the temperature of the material surface decreases, the number of micro-textures formed decreases, the shape is more complex, the volume of the micro-texture gradually decreases, and the spacing between the micro-textures also gradually decreases.
[0034] Example 3 Steps 1 to 4 of Example 3 are the same as those of Example 1, except that: Step 5: According to the filtering requirements of the nickel-based alloy mesh material and the influence of the content of each element in the material on the service life, the nanosecond pulse laser processing parameters are further optimized and adjusted to find the optimal laser processing parameter group.
[0035] The filling mode of nanosecond pulse laser is set to unidirectional filling, the number of processing times is 3, the processing power is 41W, the processing speed is 35mm / s, and the repetition frequency is 25kHz. Experiments are conducted with the increase of the pulse width of nanosecond pulse laser (250ns, 300ns, 350ns, 400ns, 450ns, 500ns), and the experimental results are tested and compared. The experimental results are tested and compared, and finally the surface morphology, pore area size, element content, micro-texture morphology state and wettability of nickel-based alloy mesh materials are obtained as the pulse width changes. See Figure Figure 4a is the surface wettability of the material when the pulse width is 250 ns in Example 3; Figure 4b is the surface wettability of the material when the pulse width is 300 ns in Example 3; Figure 4c is the surface wettability of the material when the pulse width is 350ns in Example 3; Figure 4d is the surface wettability of the material when the pulse width is 400 ns in Example 3; Figure 4e is the surface wettability of the material when the pulse width is 450ns in Example 3; Figure 4f It is the surface wettability of the material when the pulse width is 500ns in Example 3.
[0036] From the results of Example 3, it can be found that the surface morphology of the nickel-based alloy mesh material after the modification treatment gradually changes from hydrophobic to hydrophilic as the pulse width increases. This is because as the pulse width increases, the time that the laser maintains a certain power increases, the surface temperature of the material gradually increases, the number of micro-textures formed on the surface of the nickel-based alloy mesh material gradually increases, and the spacing between the micro-textures gradually increases. When droplets are deposited on the material surface, most of the droplet volume is stored in the gaps between the micro-textures. The larger the gaps between the micro-textures, the more droplet volume is stored in the gaps, the smaller the angle formed by the remaining droplets on the material surface, and the stronger the hydrophilicity of the material surface.
[0037] Example 4 Steps 1 to 4 of this embodiment 4 are the same as those of embodiment 1, except that: Step 5: According to the filtering requirements of the nickel-based alloy mesh material and the influence of the content of each element in the material on the service life, the nanosecond pulse laser processing parameters are further optimized and adjusted to find the optimal laser processing parameter group.
[0038] The filling mode of the nanosecond pulse laser was set to unidirectional filling, the number of processing times was 3 times, the processing power was 41W, the processing speed was 35mm / s, and the pulse width was 400ns. Experiments were conducted with increasing repetition frequency of the nanosecond pulse laser (22kHz, 23kHz, 24kHz, 25kHz, 26kHz, and 27kHz). Figure 5 As shown, the experimental results were tested and compared, and finally the variation patterns of the surface morphology, pore area size, element content, micro-texture morphology and wettability of the nickel-based alloy mesh material with the repetition frequency were obtained.
[0039] Example 5 Steps 1 to 4 of Example 5 are the same as those of Example 1, except that: Step 5: According to the filtering requirements of the nickel-based alloy mesh material and the influence of the content of each element in the material on the service life, the nanosecond pulse laser processing parameters are further optimized and adjusted to find the optimal laser processing parameter group.
[0040] The filling mode of nanosecond pulse laser is set to unidirectional filling, the processing power is 41W, the processing speed is 35mm / s, the repetition frequency is 25kHz, and the pulse width is 400ns. Experiments are carried out with the increase of the number of nanosecond pulse laser processing times (1 time, 2 times, 3 times, 4 times, 5 times, 6 times), see Figure 6 As shown, the experimental results were tested and compared, and finally the surface morphology, pore area size, element content, micro-texture morphology and wettability of the nickel-based alloy mesh material changing with the number of processing times were obtained.
[0041] Example 6 Steps 1 to 4 of Example 6 are the same as those of Example 1, except that: Step 5: According to the filtering requirements of the nickel-based alloy mesh material and the influence of the content of each element in the material on the service life, the nanosecond pulse laser processing parameters are further optimized and adjusted to find the optimal laser processing parameter group.
[0042] The parameters of the nanosecond pulse laser were set to: processing power of 41 W, processing speed of 35 mm / s, repetition frequency of 25 kHz, pulse width of 400 ns, and the number of processing times was set to 3 times. Experiments were carried out with the filling methods (unidirectional filling, bidirectional filling, annular filling, and arch filling) of the nanosecond pulse laser (the drawings of this embodiment 6 are omitted), and the obtained experimental results were tested and compared and analyzed, and finally the surface morphology, pore area size, element content, microtexture morphology state and wettability of the nickel-based alloy mesh material were obtained as the number of processing times varied.
[0043] In summary, the surface of nickel-based alloy mesh material was modified by nanosecond pulse laser, and parameters such as laser processing power, processing speed, repetition frequency, pulse width and processing times were adjusted. The regularity of the surface morphology, pore area size, element content, surface microtexture morphology and wettability changes of the material was studied, and finally the following conclusions were obtained: (1) With the increase of processing power: First, the surface morphology of the material. During the laser processing, the surface temperature of the material gradually increases, and thermal expansion occurs at certain intervals in the lateral direction. Each expansion point is the focus of the laser, where the laser energy is most concentrated, and the volume of thermal expansion continues to increase; due to the continuous increase in the expansion volume of the material surface, the area size of the pores continues to decrease; with the increase of processing power, the oxides on the material surface gradually increase, the oxygen content gradually increases, and the nickel content gradually decreases; for the micro-texture on the material surface, with the increase of processing power, the number of micro-textures increases, the volume increases, and the spacing between the expansion bodies increases; due to the increase in the spacing between the expansion bodies, most of the droplet volume is stored in the gap, and the contact angle formed by the remaining droplets on the material surface gradually decreases, the hydrophobicity of the material gradually weakens, and the hydrophilicity gradually increases.
[0044] (2) With the increase of processing speed: First, the surface morphology of the material gradually becomes lighter in color. Due to the shortening of processing time, the surface temperature of the material gradually decreases, the thermal expansion volume continues to decrease, and the laser energy is most concentrated at each expansion point where the laser focus is the laser focus; due to the continuous decrease in the expansion volume of the material surface, the pore area size continues to increase; with the increase of processing speed, the time the laser acts on the material surface continues to decrease, the oxide on the material surface gradually decreases, the oxygen content gradually decreases, and the nickel content gradually increases; for the micro-texture on the material surface, with the increase of processing speed, the number of micro-textures decreases, the volume decreases, and the spacing between the expansion bodies decreases. Due to the decrease in the spacing between the expansion bodies, a small part of the droplet volume is stored in the gap, and the contact angle formed by the remaining droplets on the material surface gradually increases, the hydrophilicity of the material gradually weakens, and the hydrophobicity gradually increases.
[0045] (3) With the increase of repetition frequency: first, the surface morphology of the material gradually darkens in color. As the number of photons emitted per second increases, the surface temperature of the material gradually rises, and thermal expansion occurs at certain intervals in the lateral direction. Each expansion point is the focus of the laser, where the laser energy is most intensive, and the thermal expansion volume continues to increase; as the expansion volume of the material surface continues to increase, the pore area size continues to decrease; with the increase of repetition frequency, the amount of oxides on the material surface gradually increases, the oxygen content gradually increases, and the nickel content gradually decreases; with respect to the micro-texture on the material surface, as the repetition frequency increases, the number of micro-textures increases, the volume increases, and the spacing between the expansion bodies increases; as the spacing between the expansion bodies increases, most of the droplet volume is stored in the gap, and the contact angle formed by the remaining droplets on the material surface gradually decreases, the hydrophobicity of the material gradually weakens, and the hydrophilicity gradually increases.
[0046] (4) With the increase of pulse width: First, the surface morphology of the material. As the time of maintaining a certain value increases, the surface temperature of the material rises, and thermal expansion occurs at certain intervals in the lateral direction. Each expansion point is the focus of the laser, the laser energy is the most concentrated, and the thermal expansion volume continues to increase; due to the continuous increase in the expansion volume of the material surface, the pore area size continues to decrease; with the increase of pulse width, the oxide on the surface of the material gradually increases, the oxygen content gradually increases, and the nickel content gradually decreases; for the micro-texture on the surface of the material, with the increase of pulse width, the number of micro-textures increases, the volume increases, and the spacing between the expansion bodies increases; due to the increase in the spacing between the expansion bodies, most of the droplet volume is stored in the gap, and the contact angle formed by the remaining droplets on the material surface gradually decreases, the hydrophobicity of the material gradually weakens, and the hydrophilicity gradually increases. Compared with other processing parameters, the change of pulse width has little effect on the experimental results.
[0047] (5) With the increase of the number of processing times: First, the surface morphology of the material. During the laser processing, the surface temperature of the material gradually increases, and thermal expansion occurs at a certain interval in the lateral direction. Each expansion point is the focus of the laser, where the laser energy is most concentrated, and the volume of thermal expansion continues to increase; due to the continuous increase in the expansion volume of the material surface, the area size of the pores continues to decrease; with the increase of the number of processing times, the oxides on the material surface gradually increase, the oxygen content gradually increases, and the nickel content gradually decreases; with respect to the micro-texture of the material surface, with the increase of the number of processing times, the number of micro-textures increases, the volume increases, and the spacing between the expansion bodies increases; due to the increase in the spacing between the expansion bodies, most of the droplet volume is stored in the gap, and the contact angle formed by the remaining droplets on the material surface gradually decreases, the hydrophobicity of the material gradually weakens, and the hydrophilicity gradually increases.
[0048] (6) Different filling methods also have different effects on the experimental results. According to the actual processing requirements and effects, unidirectional filling is finally selected. Unidirectional filling ensures the uniform distribution of filling lines due to its consistent filling method from left to right. In addition, unidirectional filling is simple to operate and easy to control. It is suitable for laser processing of simple patterns and texts. Path planning is simpler, which reduces the complexity of the processing process and helps to improve processing efficiency. Unidirectional filling has stronger applicability.
[0049] Through the above experiments and conclusions, combined with the filtration efficiency, filtration effect and service life of the nickel-based alloy mesh material, the optimal laser processing parameter group was finally obtained: the filling method is unidirectional filling, the processing power is 41W, the processing speed is 35mm / s, the repetition frequency is 25kHz, the pulse width is 400ns, and the number of processing times is 3 times.
Claims
1. A method for surface modification of nickel-based alloy materials based on pulsed laser, characterized in that: Follow these steps to implement: Step 1, ultrasonically cleaning and drying the nickel-based alloy mesh material to be processed; Step 2, installing the nickel-based alloy mesh material into the laser processing system to complete the pre-processing preparation work; Step 3, importing the designed processing dimensions into the laser processing system, setting preliminary processing parameters, performing preliminary processing, and measuring and comparing the nickel-based alloy mesh material after preliminary processing; Step 4, performing a wettability test on the nickel-based alloy mesh material after preliminary processing to analyze the effects of different processing parameters on the wettability of the material; Step 5: According to the filtering requirements of the nickel-based alloy mesh material and the influence of the content of each element in the material on the service life, the process parameters in the nanosecond pulse laser processing process are continuously optimized and adjusted to seek the optimal laser processing process parameter group.
2. The method for surface modification of nickel-based alloy materials based on pulsed laser according to claim 1, characterized in that: In step 1, the specific process is: The ultrasonic cleaning machine model used is JP-020S, which can thoroughly remove stains, oil stains, dust and impurities on the surface of the nickel-based alloy mesh material and in the tiny gaps.
3. The method for surface modification of nickel-based alloy materials based on pulsed laser according to claim 1, characterized in that: In step 2, the specific process is: Place the nickel-based alloy mesh material after ultrasonic cleaning flat on the stage, and press and fix the nickel-based alloy mesh material with the two pressure plates on the stage; then turn on the main switch of the nanosecond pulse laser, turn on the key switch on the control panel, and after the value displayed by the DC voltage stabilizes, start the computer and turn on the laser processing system on the monitor; next, focus by continuously adjusting the rotating ruler. When the focal length of the laser beam is adjusted, lock the rotating ruler by rotating the wrench to complete the processing preparation work for the nickel-based alloy mesh material.
4. The method for surface modification of nickel-based alloy materials based on pulsed laser according to claim 1, characterized in that: In step 3, the specific process is: First, open the control software of the nanosecond pulse laser and input the pattern information to be processed; Then, the preliminary processing parameters of the nanosecond pulse laser are set, and the preliminary processing is performed after the parameters are set; Afterwards, the nickel-based alloy mesh material that has completed preliminary processing is measured and analyzed.
5. The method for surface modification of nickel-based alloy materials based on pulsed laser according to claim 4, characterized in that: Set the preliminary processing parameters of the nanosecond pulse laser as follows: The filling method is unidirectional filling, the filling spacing is 10μm, the processing power is 10-60W, the processing speed is 10-50mm / s, the repetition frequency is 20-30kHz, the pulse width is 100-500ns, and the processing number is 1-10 times.
6. The method for surface modification of nickel-based alloy materials based on pulsed laser according to claim 4, characterized in that: The measurement analysis includes the following three aspects: First, a laser confocal microscope is used to observe and analyze the surface morphology; second, a high-precision imager is used to measure the pore area size; third, an electron microscope is used to observe and analyze the element content and the morphology of the surface microtexture.
7. The method for surface modification of nickel-based alloy materials based on pulsed laser according to claim 1, characterized in that: In step 4, the wettability is tested using a contact angle tester. The experimental process is: the nickel-based alloy mesh materials under different laser processing parameters after preliminary processing are placed on the detection platform respectively, and after adjusting the position and camera focus, 5 μL of pure water droplets are taken through a microsampler on the surface of the nickel-based alloy mesh material after preliminary processing. When the droplets spread on the micro-texture surface of the nickel-based alloy mesh material and tend to a stable state, the contact angle tester is used to measure the solid-liquid contact angle on the surface of the nickel-based alloy mesh material.
8. The method for surface modification of nickel-based alloy materials based on pulsed laser according to claim 1, characterized in that: In step 5, the specific process is: According to the changing rules of surface morphology, pore area size, element content, surface microtexture morphology and wettability of nickel-based alloy mesh materials, the single factor variable method was adopted, keeping all other variables unchanged, and the influence of each variable on the result was studied in turn. Through comparative analysis, the combination of laser processing process parameters was finally obtained.
Citation Information
Patent Citations
Laser texture method for improving abrasion resistance of nichrome surface
CN106862773A
Laser stitch welding technology for filter screen
CN107378247A
Ultrafast laser cutting method for miniature oil filter screen of engine
CN113996952A
Laser welding method for aluminum alloy / nickel-based alloy or nickel dissimilar material
CN114505577A
Nickel-based alloy material
CN116134167A